Multiple Intellegences-Based & Learning Innovation Towards Era 5.0 - Maja, Gergely; María-José, Chandrasekaran; Anindya, Shuxiang; Malin, Anna; Karin, Larasati (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The development and advancement of technology at this time is very beneficial for human life, especially in the world of education where with the development of this technology students are expected to improve their performance in lessons. But mostly what happens at this time is the lack of teacher attention to the intelligence possessed by the child. Every child certainly has different intelligence, for that teachers are required to be able to understand and analyze the intelligence possessed by their students. With this multiple intelligence-based learning innovation, teachers can improve learning outcomes according to the abilities and intelligence possessed by each child. The purpose of this research is to find out how multiple intelligence-based learning is appropriate in the teaching and learning process. The method used from this research is quantitative method by using Google From and WhatsApps application. The results of this study indicate that multiple intelligence-based learning is very well applied in learning. The conclusion of this study explains that the application of multiple intelligence-based learning is very good for improving children's learning outcomes so that children's achievement can increase from the previous one. The limitation of this research is that researchers do not make how many percent of educators who have been able to apply multiple intelligence in learning and the extent of development that has been achieved by educators, for that it is hoped that further researchers can conduct more complete research